2016
DOI: 10.1097/ftd.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Variable Linezolid Exposure in Intensive Care Unit Patients—Possible Role of Drug–Drug Interactions

Abstract: Drug exposure after standard doses of linezolid is highly variable and difficult to predict in ICU patients, and therapeutic drug monitoring seems advisable. PK drug-drug interactions might partly be responsible and should be further investigated; protein binding appears to be stable and irrelevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…In the last year, several authors further supported the hypothesis that TDM might represent the way forward for optimizing linezolid therapy in specific subpopulations of patients .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the last year, several authors further supported the hypothesis that TDM might represent the way forward for optimizing linezolid therapy in specific subpopulations of patients .…”
Section: Discussionmentioning
confidence: 92%
“…We supposed that the interindividual variability of linezolid C min may be related mainly to drug–drug interactions . Other authors suggested that linezolid C min may be influenced also by the degree of renal function , by the severity of critical illness or even by some other factors .…”
mentioning
confidence: 92%
“…Based on a population kinetic approach, a dosing schedule of 450 mg linezolid thrice daily has been suggested, in order to avoid high peak plasma concentrations during multiple dosing [10]. Based on the result of the present study, an alternative and practicable twice daily dosing schedule could include a loading dose of 600 mg or even 900 mg, accounting for the higher volume of distribution in obese patients and the slower diffusion into the tissue, followed by standard dosing of 600 mg linezolid twice daily, accounting for the similar clearance in both groups, and preferably administered as prolonged infusion, starting, e.g., after 8 h instead of 12 h. Regarding further dose adjustments during multiple dosing in critically ill patients, therapeutic drug monitoring is advised due to the high variability of linezolid plasma concentrations in these patients [27,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Linezolid was determined by a validated HPLC-UV method, as described previously [26,27]. Sample treatment for the determination of total linezolid included the deproteinization of plasma with perchloric acid, and microdialysate was directly injected into the column.…”
Section: Drug Analysismentioning
confidence: 99%
See 1 more Smart Citation